The Homily on The [Cursed] Fig-Tree and the Parable of the Vineyard by John Damascene in Mediaeval Slavonic Literature [Preliminary Observations] - Данова, Цветомира (Poznańskie Studia Slawistyczne, 2018)
The Slavonic version of the homily dedicated to The (Cursed) Fig-Tree and the Parable of the Vineyard by John Damascene has not been so far object of an archeographic-textological study. The present study gives the initial observations on the reception of that Byzantine work in Mediaeval Slavonic Literature. The work centred mainly on the South Slavonic manuscript tradition, while the East Slavonic manuscript tradition represented by the text from the well-known Uspensky Miscellany was used as a starting point and as a basis for comparison during the analysis. The study showed that in Mediaeval Slavonic Literature the homily dedicated to The (Cursed) Fig-Tree and the Parable of the Vineyard by John Damascene has been disseminated through three different Slavonic translations, one redaction, and one contaminated version.